imulasi Prototype Pembangkit Listrik Tenaga Mikrohidro Turbin Crossflow Ditinjau dari Ketinggian, Debit dan Arah Aliran - Ridwan, K.A; Lestari, Sutini Pujiastuti; Rusnadi, Irawan; ., Erlinawati; Rahayu, Atika; Mahendra, Evando; Pratama, Wahyudi (KINETIKA, 2021)
The energy crisis prompted the Indonesian government to change the paradigm towards new and renewable energy, from alternative energy to main energy. In order to overcome the electrical energy crisis, then conducted research on new and renewable energy. Utilization of microhydro based energy generation into one solution to be applied in effort to overcome this crisis. Microhydro power plant (PLTMH) is carried out by utilizing flow velocity (river flow) or head potential (waterfall) with water turbine connected to a generator so that it can convert mechanical energy from the turbine into electrical energy. Type of turbine used is crossflow turbine. This simulation is by varying the head potential (1.6 m, 1.8m, 2 m, 2.2 m, 2.4 m) and the direction of flow (horizontal overshoot, vertical overshoot, and undershoot) generated electrical energy. Based on the research results, the optimal flow direction horizontal overshoot flow which produces flow discharge 20 liter/min, the electrical energy 16 watt, and at height of 2.4 meters and the electrical energy15.3 watt.